How the Nouvelle Vague Invented the DVD: Cinephilia, new waves and film culture in the age of digital dissemination - Hagener, Malte (2014)
Whereas the currently emerging configurations of audiovisualcy in the age of digital networks are often addressed in terms of absolute novelty and innovation, this article wishes to shift the focus slightly, articulating instead the new in terms of the old. This essay proposes the argument that it was within the Nouvelle Vague and the French film culture of the 1960s that the DVD was “invented”. Obviously, this is a contrafactual argument, but if we understand the DVD as a discursive construction articulating a specific perspective on film, then the DVD simulates and emulates some key features of 1960s cinephilia that emerged within the context of the new waves. On the other hand, the Nouvelle Vague is understood as a broad discursive movement encompassing all segments of the institution cinema rather than five auteur-directors — Truffaut, Godard, Chabrol, Rohmer and Rivette — and their respective films. By arguing for the continuing importance of film history and culture, this article wishes to underline the fact that technological as well as aesthetic transformations are central to our understanding of media culture.